Local transformation in rural Vietnam: A commune level analysis - Ulrik Beck (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This study documents the local transformation of rural Vietnamese communes in 12 different provinces from 2006 to 2014. Three key areas are considered, namely occupational and agricultural choice; provision of public goods and infrastructure as well as land markets. While many areas showed great improvements over the period, the level and the speed of transformation was also found to vary between different geographical regions. While communes report fewer problems in 2014 than in 2006, there has been a marked increase in the number of communes who say climate change is an issue. Officials expect this to increase even more going forward.
Keywords: O13; O18; Q15; R11; 330; Vietnam; occupational choice; land markets; infrastructure